2013
DOI: 10.1002/anie.201305761
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Claw: A Dynamic Cavitand Host

Abstract: Up for grabs: A modular receptor comprises a hexaazatriphenylene "platform" and three imide residues on its concave side carrying flexible alkane chains. The chains not only populate the host's cavity but can also extend and can grab an appropriately sized and shaped guest in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Moreover, the strategy for obtaining a synthetic molecule consists of employing methods of computational chemistry to design a desired host followed by experimental optimization of its synthesis. [32] So, we expect that the theoretical prediction of this work may be useful for the future experimental study and may be realized in the laboratory.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the strategy for obtaining a synthetic molecule consists of employing methods of computational chemistry to design a desired host followed by experimental optimization of its synthesis. [32] So, we expect that the theoretical prediction of this work may be useful for the future experimental study and may be realized in the laboratory.…”
Section: Introductionmentioning
confidence: 80%
“…More important, this kind of host may facile release fullerene guest by the transformation of the configurations between trans‐ form and cis ‐form of the azobenzene groups upon the external stimuli of photoirradiation. Moreover, the strategy for obtaining a synthetic molecule consists of employing methods of computational chemistry to design a desired host followed by experimental optimization of its synthesis . So, we expect that the theoretical prediction of this work may be useful for the future experimental study and may be realized in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Recently, Haley and Johnson et al demonstrated the alteration of anion binding selectivity and colorimetric response upon protonation of a series of 2,6-bis(2-anilinoethynyl)pyridine derivatives. [20][21][22] As a highly symmetric scaffold, hexaazatriphenylene (HAT) exhibits extensive applications [23] in a wide range of emerging areas including sensors, [24][25][26] self-assembled soft matter, [27][28][29][30] and optical materials. [31] However, most of the reported host-guest studies concerning HAT have generally focused on specific recognition phenomena originated from metal coordination interaction between pyridine moieties and metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Further light-induced oxidation coupling reaction led to thienyl-fused compound 2.T heir photophysical and electrochemical properties ands elf-assembly behavior have been investigated by UV/Vis,fluorescence, and 1 HNMR spectroscopies, cyclic voltammetry (CV), scanning electron microscopy (SEM), and powder X-ray diffraction (PXRD). Although the difference in compounds 1 and 2 only lie in one single bond that connectst he two thienyl segments, they displayed remarkably different properties, revealing an interesting structure-property relationship.In recent years, p-conjugated molecules, especially those with fused rings and containing heteroatoms such as nitrogen, boron,s ulfur or selenium, [1] have attracted attention because of their extensive applications in ar ange of emerging areas including sensors, [2] self-assembled soft matter, [3] opticalm aterials, [4] and electronic devices.[5] Among the numerousa romatic molecules, hexaazatriphenylene (HAT) has been extensivelye xplored not only as af undamentalm otif to prepare extended 2D N-substituted polycyclica romaticsb ut also as ab asic building block to fabricate av ariety of supramolecular architectures and metal complexes.[6] Due to their electron-deficient, discotic shape and rigid skeleton, HATd erivatives exhibit as trong p-p stacking tendency,w hich makes them excellent candidates for the constructiono fw ell-ordereds upramolecular architectures, [7] liquid crystals, [8] n-types emiconductors, [9] sensors, [10] nonlinearo ptical chromophores, [11] and microporous polymers. [12] HATi sahighlys ymmetric scaffold.…”
mentioning
confidence: 99%
“…[5] Among the numerousa romatic molecules, hexaazatriphenylene (HAT) has been extensivelye xplored not only as af undamentalm otif to prepare extended 2D N-substituted polycyclica romaticsb ut also as ab asic building block to fabricate av ariety of supramolecular architectures and metal complexes. [6] Due to their electron-deficient, discotic shape and rigid skeleton, HATd erivatives exhibit as trong p-p stacking tendency,w hich makes them excellent candidates for the constructiono fw ell-ordereds upramolecular architectures, [7] liquid crystals, [8] n-types emiconductors, [9] sensors, [10] nonlinearo ptical chromophores, [11] and microporous polymers. [12] HATi sahighlys ymmetric scaffold.…”
mentioning
confidence: 99%